2021
DOI: 10.29271/jcpsp.2021.09.1120
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Digital Pathology in Developing Countries: From Benefits to Challenges

Abstract: Digital pathology and the use of artificial intelligence constitute undisputedly the future of modern pathology. The outcomes and benefits of the whole slide imaging are beyond the scope of traditional microscopy, which the pathologists were using for decades. COVID-19 pandemic has further highlighted the importance of digital pathology as it offers the pathologists to work from their place of comfort and bridges the gap of physical barriers. In addition to the many advantages, there are certain limitations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Further costs include hardware (high-resolution display screens and high-performance computers), additional software, IT infrastructure and personnel. In addition to financial issues, low-and middle-income countries tend to suffer from a general shortage of pathologists which often prefer to practice in urban agglomerations, whereas a large proportion of the population lives in rural areas (31). Therefore, unfortunately, the wealth of a particular region will influence potential applications of digital pathology.…”
Section: Globally Relevant Issuesmentioning
confidence: 99%
“…Further costs include hardware (high-resolution display screens and high-performance computers), additional software, IT infrastructure and personnel. In addition to financial issues, low-and middle-income countries tend to suffer from a general shortage of pathologists which often prefer to practice in urban agglomerations, whereas a large proportion of the population lives in rural areas (31). Therefore, unfortunately, the wealth of a particular region will influence potential applications of digital pathology.…”
Section: Globally Relevant Issuesmentioning
confidence: 99%
“…47 This will possibly change with an increased awareness of DP applications and benefits and its widespread adoption in upcoming years. 55,57,58 The reason why more of the included studies validated ML models for diagnosis or classification purposes is unknown. However, it may be partly explained by the fact that ML models used to predict biomarkers were excluded during the selection process.…”
Section: Interpretation and Implications Of The Resultsmentioning
confidence: 99%
“… 47 This will possibly change with an increased awareness of DP applications and benefits and its widespread adoption in upcoming years. 55 , 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…These include operating costs, data security as well as user acceptance. Additionally, continuous training of pathologists regarding principles and limitation of digital pathology, sustainable internet connectivity, continuous bi-directional communication, and support from the institutional leadership are key to the success of telepathology programs [ 33 36 ]. A study comparing the cost for telepathology and a visiting pathologist services has revealed that establishing and running telepathology services were cheaper compared to hiring a visiting pathologist [ 37 ].…”
Section: Discussionmentioning
confidence: 99%